Book review: Mathematical competitions and classroom collaboration: antonyms or a new direction for research on teacher beliefs? - Sriraman, Bharath; Steinthorsdottir, Olof (NOMAD Nordic Studies in Mathematics Education, 2007)
Tine Wedege and Jeppe Skott (2006), Changing views and practices: a study of the KappAbel mathematics competition. Research report, Norwegian Center for Mathematics Education & Norwegian University of Science and Technology, Trondheim. ISBN 82-471-6040-4